KUALITAS AIR DAN TANAH TAMBAK UDANG YANG MENDAPAT PERLAKUAN PENGERINGAN DAN AERASI SETELAH PENGGENANGAN - Bambang Triyatmo; Bostang Radjagukguk; Iwan Yusuf Bambang Lelana (Jurnal Perikanan Universitas Gadjah Mada, 1996)
The experiment was carried out to evaluate the water and soil quality of pond, which were subjected to drying and aeration after inundation. The objective of the experiment was to find out which soil drying and water aeration treatments were the best for shrimp culture.The soil used was obtained from an intensive shrimp pond and sea water was collected  from pond area in jepara coast. The soil drying treatments consisted of drying the wet soil under the sun to air dry condition, field capacity condition and water saturated condition. The soil drying treatments were carried out for 64 days. The aeration treatments after inundation consisted of with aeration and without aeration. Soil less sea water also was prepared as control. The aeration treatments were carried out for 64 days. The soil and water quality were  observed during soil drying and water aeration treatments.Result of this experiment indicated that drying the pond bottom soil until field capacity condition gave the highest rate of organic matter decompotition followed by air dried soil, then water saturated oil. The decompotition of soil organic matter in the field capacity condition reached optimum on day 8 to 16. The pond bottom soil in water saturated condition contained lower NH3, NO2- and H2S than ind dried soil. Aeration gave better condition than the non aeration one. It seemed the best water quality condition for shrimp fry stocking occurred 4-8 days after inundation combined with aeration.